Mitral Valve Annuloplasty Ring Dehiscence Diagnosed Intraoperative With Real-Time 3D Transesophageal Echocardiogram. (24th June 2014) - Castellon-Larios, Karina; Zuleta-Alarcon, Alix; Flores, Antolin; Humeidan, Michelle; Springer, Andrew N.; Essandoh, Michael
Mitral annular calcification (MAC) is often a result of the accumulation of lipids around the annulus, which can lead to degeneration and calcification of the valve. Multiple risk factors have been associated with the progression of MAC and life-threatening complications such as the early mitral valve annuloplasty dehiscence. Our case describes the different risk factors for annuloplasty dehiscence in a patient with severe MAC, as well as the importance of its early recognition intraoperatively with 3D transesophageal echocardiography.